Trends and Hotspots in Sustainable Management Research: A Scopus-Based Bibliometric Analysis - Adhikari, Pitri Raj; Neupane, Dasarath (Academia Journal of Research and Innovation, 2025)
Background: Scientific publications in sustainable management have grown rapidly in recent years. Given this expansion, it is essential to conduct a bibliometric analysis to identify research trends and thematic hotspots in the field. Methods: A systematic literature review design was employed using data extracted from the Scopus database. The analysis was conducted using R Studio and the Bibliometrix package to visualize trends and map research themes. Results: The analysis revealed 231 documents published across 98 sources, with an annual growth rate of 7.25%. A total of 857 authors contributed, with an average of 3.88 co-authors per document and 33.77% international collaboration. Three major thematic clusters were identified in sustainable management literature. Thematic mapping highlighted niche, motor, basic, and emerging themes. A thematic evolution was observed from general sustainable management to more focused areas such as supply chain management, environmental impact, and circular economy. Conclusion: The study provides an overview of the intellectual structure and thematic development of sustainable management research. It identifies key areas of focus and evolution offering a roadmap for future investigations in the field. Novelty: This study uniquely reveals strategic shifts toward the circular economy and environmental impact, aspects rarely highlighted in earlier research.